2012
DOI: 10.1113/jphysiol.2012.228890
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinal fatigue after normoxic and hypoxic exercise in humans

Abstract: Inadequate cerebral O2 availability has been proposed to be an important contributing factor to the development of central fatigue during strenuous exercise. Here we tested the hypothesis that supraspinal processes of fatigue would be increased after locomotor exercise in acute hypoxia compared to normoxia, and that such change would be related to reductions in cerebral O2 delivery and tissue oxygenation. Nine endurance-trained cyclists completed three constant-load cycling exercise trials at ∼80% of maximal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
167
3
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(203 citation statements)
references
References 57 publications
23
167
3
7
Order By: Relevance
“…Despite the intense exercise (75% Wmax) used in our study not be considered fatiguing, the intensity and duration that were used probably were enough to promote accumulation of fatigue metabolites and corresponding increased firing of muscle metabosensitive receptors, or other acute exercise-induced responses that are common to fatiguing exercise 5 . Although the precise cellular mechanisms underlying post-exercise MEP depression are unclear, Sammi, Wassermann, Hallett 22 hypothesize that exercise may modify synaptic transmission within the motor cortex for several minutes in a way In contrast to our results, previous TMS studies [23][24] that used cycling exercise of similar high intensity (80% Wmax) and longer duration (~45min) reported no changes in MEP responses measured either in vastus lateralis 23 or rectus femoris muscles…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the intense exercise (75% Wmax) used in our study not be considered fatiguing, the intensity and duration that were used probably were enough to promote accumulation of fatigue metabolites and corresponding increased firing of muscle metabosensitive receptors, or other acute exercise-induced responses that are common to fatiguing exercise 5 . Although the precise cellular mechanisms underlying post-exercise MEP depression are unclear, Sammi, Wassermann, Hallett 22 hypothesize that exercise may modify synaptic transmission within the motor cortex for several minutes in a way In contrast to our results, previous TMS studies [23][24] that used cycling exercise of similar high intensity (80% Wmax) and longer duration (~45min) reported no changes in MEP responses measured either in vastus lateralis 23 or rectus femoris muscles…”
Section: Discussioncontrasting
confidence: 99%
“…One reason for this discrepancy might be due the place where the corticospinal excitability was evaluated, in the cortical representation area of non-exercised muscle (our study) in contrast to exercised muscle (previous studies) [23][24] . However, contrary to this hypothesis, Takahashi et al 25 showed that intense exercise of leg muscles leads to pronounced effects on the corticospinal and corticocortical excitability of two non-exercised arm muscles (FID and biceps brachi).…”
mentioning
confidence: 65%
“…The gradual decline in CBF with exercise intensity above a certain threshold also reduces cerebral oxygenation. This has been speculated to lead to centrally mediated fatigue (17,33). A unique feature of CO 2 supplementation is that whereas MCAv mean and cerebral oxygenation are increased, oxygenation of the exercising skeletal muscles remains unaffected by the intervention (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Работами группы S. Goodall (2010Goodall ( , 2012) на гонщиках-велосипедистах было показано, что в процессе циклического упражнения до отказа (~80 % от максимальной рабочей нагрузки) у од-них и тех же лиц при гипоксии (FiO 2 ~0,13 и выше) длительность работы значительно уменьшается (Goodal et al, 2012). Дополнительное центральное утомление при жесткой гипоксии не обусловлено измененной кортикоспинальной возбудимостью, но есть проявление супраспинального утомления, которое играет возрастающую роль при жесткой (FiO 2 0,1 и S a O 2 74 %) гипоксии (Goodall et al, 2010).…”
Section: цнс при гипоксииunclassified
“…Такое уменьшение в кортикальной произвольной активации сразу по-сле упражнения показывает, что напряженная ра-бота при жесткой гипоксии уменьшает способность двигательной коры управлять мышцами разгибате-лями ног. Пока работы ряда исследований наводи-ли на мысль, что центральное моторное управление может быть затронуто при жесткой гипоксии (Amann et al, 2007;Subudhi et al, 2007Subudhi et al, , 2008Subudhi et al, , 2009Vogiatzis et al, 2011), работа (Goodal et al, 2012) первая дей-ствительно продемонстрировала увеличение супра-спинального утомления, проявляющегося как ре-зультат мышечной работы в условиях гипоксии.…”
Section: цнс при гипоксииunclassified